Cognitive benefits of last night's sleep: daily variations in children's sleep behavior are related to working memory fluctuations. (23rd July 2014) - Könen, Tanja; Dirk, Judith; Schmiedek, Florian
<x xml:space="preserve">Abstract</x> Background Recent studies have suggested substantial fluctuations of cognitive performance in adults both across and within days, but very little is known about such fluctuations in children. Children's sleep behavior might have an important influence on their daily cognitive resources, but so far this has not been investigated in terms of naturally occurring within‐person variations in children's everyday lives. Methods In an ambulatory assessment study, 110 elementary school children (8–11 years old) completed sleep items and working memory tasks on smartphones several times per day in school and at home for 4 weeks. Parents provided general information about the children and their sleep habits. Results We identified substantial fluctuations in the children's daily cognitive performance, self‐reported nightly sleep quality, time in bed, and daytime tiredness. All three facets were predictive of performance fluctuations in children's school and daily life. Sleep quality and time in bed were predictive of performance in the morning, and afternoon performance was related to current tiredness. The children with a lower average performance level showed a higher within‐person coupling between morning performance and sleep quality. Conclusions Our findings contribute important insights regarding a potential source of performance fluctuations in children. The effect of varying cognitive resources should be investigated further because it might impact children's daily social, emotional, and learning‐related functioning. Theories about children's cognitive and educational development should consider fluctuations on micro‐longitudinal scales (e.g., day‐to‐day) to identify possible mechanisms behind long‐term changes.